Cilacap (1830-1942) : bangkit dan runtuhnya suatu pelabuhan di Jawa - Zuhdi, Susanto (Jakarta : Kepustakaan Populer Gramedia, 2002)
History of Cilacap as a harbor for traffic trade in southern part of Jawa
[Rujukan] : p. 191-195
Keywords: Harbors -- Indonesia -- Cilacap -- History; Cilacap (Indonesia) -- History